Diagnostic and therapy of severe Clostridioides difficile infections in the ICU. Issue 5 (October 2020) - Guery, Benoit; Barbut, Frédéric; Tschudin-Sutter, Sarah
Abstract : Purpose of review: The purpose of the review is to provide all the recent data focusing on the diagnostic and treatment of Clostridioides difficile infection in patients admitted in the ICU. Recent findings: In the ICU, diagnosis remains complicated with a large number of alternative diagnosis. The treatment classically relies on vancomycin but fidaxomicin and fecal microbiota transplantation are now potential solutions in selected indications. Summary: Data on ICU-related CDI remain limited and conflicting. To date, there is no unique and simple way to obtain a diagnosis for CDI, the combination of clinical signs and a two-step testing algorithm remains the recommended gold-standard. Two molecules can be proposed for first line treatment: vancomycin and fidaxomicin. Although metronidazole may still be discussed as a treatment option for mild CDI in low-risk patients, its use for ICU-patients does not seem reasonable. Several reports suggest that fecal microbiota transplantation could be discussed, as it is well tolerated and associated with a high rate of clinical cure. CDI is a dynamic and active area of research with new diagnostic techniques, molecules, and management concepts likely changing our approach to this old disease in the near future.